2013
DOI: 10.1002/jcu.22093
|View full text |Cite
|
Sign up to set email alerts
|

Telesonography: Virtual 3D image processing of remotely acquired abdominal, vascular, and fetal sonograms

Abstract: Telesonography allowed untrained operators to scan and transfer the US volume datasets over the Internet to an expert center where an expert sonographer could navigate through the reconstructed US volume and visualize sonograms of diagnostic quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Although it requires more time, it has been shown that 3D fetal liver volume is also correlated with gestational age (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Although it requires more time, it has been shown that 3D fetal liver volume is also correlated with gestational age (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…This 3D reconstruction program, of which the diagnostic accuracy for general abdomen ultrasound was estimated at 91% in a previous study (6), enables the expert to review the images sent by the untrained person at a later time and make a radiological diagnosis. Ultrasonography involves a degree of technical skill and precision, and thus it is quite operator dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a sonographer at the patient center, an expert is able to make a radiological diagnosis in delayed time from ultrasound video sequences sent by an untrained user, with the use of the 3D virtual navigation program ECHO-CNES (Unité de Médecine et Physiologie Spatiales de Tours) (6). For tele-ultrasound, the computer at the patient center (isolated site) is beforehand connected to the ultrasound device via a video converter/USB (Pinnacle for example).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we observed the presence of imaging informatics publications released in 2014 (N=4). These publications described the improvement of imaging services by integrating systems, reducing cost, using mobile devices, applying new imaging techniques in LMICs, and exploring new methods to identify and compare data in images [120][121][122][123][124]. Reviewers also identified an additional theme related to emergency services supported by information systems in LMICs [125][126][127].…”
Section: Ojphimentioning
confidence: 99%